Analisis Kemampuan Berpikir Kritis Matematis dan Motivasi Belajar Siswa pada Materi Barisan dan Deret Aritmatika - Handayani, Netti; Mulyono, Dodik; Charli, Leo (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to analyze students' mathematical critical thinking ability and learning motivation on the topic of Arithmetic Sequences and Series among grade X students at SMA Negeri Rupit. The research employed a descriptive qualitative method supported by quantitative data. The participants were 36 students consisting of 16 males and 20 females. Data were collected through a mathematical critical thinking test, learning motivation questionnaire, semi-structured interviews, and classroom observations. The results revealed that students' mathematical critical thinking ability was in the moderate category with an average score of 60.18%. Learning motivation was categorized as low with an average of 55.40%. The conclusion is there was a positive relationship between critical thinking ability and learning motivation. It is recommended that mathematics learning should implement Problem-Based Learning (PBL) and Contextual Teaching and Learning (CTL) models combined with STEM-based media to simultaneously enhance students' critical thinking skills and learning motivation. Keywords: Arithmetic Sequences and Series, Learning Motivation, Mathematical Critical Thinking Ability